A Review on Performance of the IC Engine Using Alternative Fuels - Manikandan, J.; Adhithyan, V. (International Journal of Psychosocial Rehabilitation, 2019)
The internal combustion (IC) engine is a heat engine that converts chemical energy into mechanical energy, usually made available on a rotating output shaft. Chemical energy of the fuel is first converted to thermal energy by means of combustion or oxidation with air inside the engine. This thermal energy raises the temperature and pressure of the gases within the engine, and the high pressure gas then expands against the mechanisms of the engine. This expansion is converted by the mechanical linkages of the engine to a rotating crankshaft, which is the output of the engine. The crankshaft, in turn, is connected to a transmission and/or power train to transmit the rotating mechanical energy to the desired final use. For engines this will often be the propulsion of a vehicle. Previous work has concentrated on the engine performance using the different alternative fuel for a particular time period. This period considered for testing the engine performance cannot be compared with actual running of the for the specified life of Automobile. From the published literature it is clearly observed that the effect of using alternative fuel on the design and life and the efficiency on IC engine parts like combustion chamber, liner, piston, piston rings are not addressed. Here an attempt is made to design and develop IC engine parts that are most suitable for alternate fuels that last longer without affecting the performance of the Engine. Some of the results presented are the indication of the scope for considering this research work to be done in detail